Erythrococca kaokoensis (Euphorbiaceae), a new species from Namibia and Angola - Swanepoel, Wessel (Phytotaxa, 2019)
Erythrococca kaokoensis, here described as a new species, is only known from the mountains along the Kunene River in the Kaokoveld Centre of Endemism, southwestern Angola and northwestern Namibia. These shrubs or small trees grow among rocks of anorthosite, gneiss or limestone. Diagnostic characters for E. kaokoensis include the leaves that are subcordate or lanceolate to ovate, rarely elliptic, drying dark green, yellow-green, blue-green or violet to black, and the interruptedly racemose or subpaniculate inflorescences with flowers in clusters along the axis. A comparison of some of the more prominent morphological features to differentiate between E. kaokoensis and its possible nearest relative, E. trichogyne, is provided.